Is ResonantAcoustic Mixing® (RAM) a Game Changer for Manufacturing Solid Composite Rocket Propellants?. Issue 1 (7th October 2021) - Wright, Christopher J.; Wilkinson, Peter J.; Gaulter, Sally E.; Fossey, Donald; Burn, Andrew O.; Gill, Philip P.
Abstract: This study is a structured literature review of published ResonantAcoustic® Mixing (RAM) literature, considering the benefits and constraints of using RAM. Focussing on how this will affect the future production of rubbery composite rocket propellants. The main benefits of RAM were found to be shorter mixing time, versatility of mixing and ability to mix higher viscosities than conventional mixers. Facilitating the next generation of composite propellants with improved performance and mechanical properties. Mixed in‐situ RAM overcomes viscosity limitations by removing the casting process and has safety and environmental benefits, but does need to be tested at larger production scales. The implications of RAM production on the energetics qualification process was considered. A new framework was discussed based on understanding the entire product development process including ingredient properties, manufacturing processes, and linking this to product performance; through adoption of a digital twin approach with in‐situ monitoring. Future R&D focuses on process and material control through a validated model of the mixing mechanisms, linked to material properties and output performance. Validation with scaled up comparative studies and continuous in‐situ monitoring. A full list is provided in the conclusions. Overall RAM offers numerous benefits to mixing existing and new materials with large savings in time, cost, improved safety and is more environmentally friendly. Abstract :